An Analysis of Ideological Construction of Soekarno’s twelve good expressions of the selected political speeches - Suswanto Ismadi Megah; Siti Noor Fazelah Mohd. Noor (CAHAYA PENDIDIKAN, 2021)
This study attempted to investigate ideological construction of President Soekarno realized his good expressions in selected speeches during his rule. This study was to identify what kinds of Jokowi tends to use one utterance compared others. This study applied transitivity analysis of systemic functional linguistics theory of Halliday, particularly transitivity system as a tool for analysis, more specific process of transitivity. The data obtained from President Sukarnos’ twelve good expressions of the selected speeches during 1945-1966. The data was downloaded, then analyzed qualitatively using descriptive approach. The study found that the Material process positioned considered as the most occurrences, it means that President Soekarno wants to give his good image that he is a hard worker president to build the country. These have constructed Sukarno Ideology that as the young Indonesian people is needed to work to achieve their high dream to build the nation more prosperous.s.